Crude protein levels for juvenile pirarucu - Ituassú, Daniel Rabello; Filho, Manoel Pereira; Roubach, Rodrigo; Crescêncio, Roger; Cavero, Bruno Adan Sagratzki; Gandra, André Lima (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to verify the effect of four protein levels on pirarucu, Arapaima gigas, growth performance. One hundred and twenty pirarucu juveniles, with an average weight of 120.6±3.5 g, were stocked into 12 floating cages with 1 m3 (ten fish per cage), in a complete randomized design with four treatments (32.7%, 39.3%, 43.4% and 48.6% crude protein), in three replicates each. After 45 days, results showed that diet with highest protein level (48.6%) produced a better weight gain, specific growth rate, and differentiated body composition. Feed conversion and protein efficiency ratios did not show any differences among treatments. The dietary protein level required to produce maximum growth is 48.6%.